Design and Implementation of an Agricultural Commodity Area Data Collection System Using the Waterfall Method - Elifati, Elya; Sufaidah, Siti; Sifaunajah, Agus (KH. A. Wahab Hasbullah University, 2025)
Agriculture plays a crucial role in a country's economy, not only as a food provider but also as a driver of economic growth, earning foreign exchange through the exports of agricultural products. This research aims to analyse the status of the continent, preserve agrarian production data collection, and develop and disseminate the effectiveness of a technology-based agricultural product data collection information system. This research employs a development method known as the waterfall approach, a methodology commonly used in descriptive-qualitative research. This method is a software development process carried out sequentially, where progress is seen as the air that continues to flow downwards (like a waterfall) through the phases of planning, modelling, implementation (construction), and testing. The result of this research is a system implementation, which at the system design stage is converted into program code that can be run. This will explain the implementation process of the Agricultural Commodity Area Data Collection Information System.